2013
DOI: 10.1007/s00280-013-2364-x
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic role of microRNA polymorphisms in patients with advanced esophageal squamous cell carcinoma receiving platinum-based chemotherapy

Abstract: Taken together, these findings indicate that miRNA polymorphisms may predict prognosis in advanced ESCC patients receiving platinum-based chemotherapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
31
0
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(33 citation statements)
references
References 36 publications
0
31
0
2
Order By: Relevance
“…A growing body of evidence suggests that single nucleotide polymorphisms (SNPs) in pre-miRNA genes may interfere with the mature processing or the degradation of miRNA by compromising the secondary structure and causing a reduction of the amount of mature miRNA, which attenuates or abolishes the inhibition of the target genes [14][15][16]. Furthermore, functional SNPs located in pre-miRNA may be associated with altered susceptibility to numerous diseases, including cancer, reproductive disorders and degenerative diseases [17,18]. MiR-125a is significantly down regulated in the nucleus pulposus cells of the patients diagnosed with IDD [19], but the downstream mediators and signaling pathways have not been identified.…”
Section: Introductionmentioning
confidence: 99%
“…A growing body of evidence suggests that single nucleotide polymorphisms (SNPs) in pre-miRNA genes may interfere with the mature processing or the degradation of miRNA by compromising the secondary structure and causing a reduction of the amount of mature miRNA, which attenuates or abolishes the inhibition of the target genes [14][15][16]. Furthermore, functional SNPs located in pre-miRNA may be associated with altered susceptibility to numerous diseases, including cancer, reproductive disorders and degenerative diseases [17,18]. MiR-125a is significantly down regulated in the nucleus pulposus cells of the patients diagnosed with IDD [19], but the downstream mediators and signaling pathways have not been identified.…”
Section: Introductionmentioning
confidence: 99%
“…Among these 20 miRNAs, 13 miRNAs, such as miR-16 [8], miR-93 [9], miR-200c [10], miR-25-3p [11], miR-34a [12], miR-181a [13], miR-107 [14], miR-103a [15], miR-151a [16], miR-149 [17], miR-550a [18], miR-378a [19], and miR-30c [20], have been associated with the malignant potential of esophageal cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, a function SNP in miRNA genes may affect many signaling pathways by altering the expression levels of thousands of genes (Wu et al 2014). Previous studies have shown that SNPs in miRNA genes are associated with the susceptibility to many disease, including cancer (Omrani et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Since single nucleotide polymorphisms (SNPs) located in pre-miR genes may directly affect the miRNA maturation and expression, and the binding to target mRNAs, and subsequently affect the expression of target genes (Wu et al 2014). Therefore, a function SNP in miRNA genes may affect many signaling pathways by altering the expression levels of thousands of genes (Wu et al 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation